Analysis of the Influence of Competence, Compensation, and Workload on Employee Performance at PT Waruna Shipyard Indonesia - Simanjuntak, Naomi Syallom Chatrin; Pratama, Siswa; Setiawan, Abdi (Jurnal Fokus Manajemen, 2026)
This study aimed to examine the effects of competence, compensation, and workload on employee performance at PT Waruna Shipyard Indonesia. The population of this study consisted of 413 employees, with a sample of 81 respondents determined using the Slovin formula. This study used primary quantitative data collected through questionnaires and processed using SPSS version 24. The analytical technique employed was multiple linear regression analysis. The results showed that competence, compensation, and workload, both partially and simultaneously, had positive and significant effects on employee performance at PT Waruna Shipyard Indonesia. Competence had a regression coefficient of 0.572, a t-value of 4.052, and a significance value of 0.000. Compensation had a regression coefficient of 0.244, a t-value of 2.975, and a significance value of 0.004. Workload had a regression coefficient of 0.247, a t-value of 2.542, and a significance value of 0.013. The F-test results showed an F-value of 142.478 with a significance value of 0.000. The t-table value was 1.991 and the F-table value was 2.723, indicating that t-count was greater than t-table and F-count was greater than F-table with a significance value below 0.05. Thus, Ha was accepted and Ho was rejected, indicating a significant effect. These findings indicated that hypotheses H1, H2, H3, and H4 were accepted and empirically proven, as the results were consistent with the proposed hypotheses. The most dominant variable influencing employee performance was competence, as it had the highest regression coefficient and t-value. Approximately 84.1% of employee performance was explained by competence, compensation, and workload, while the remaining percentage was influenced by other factors. Employee performance had a very strong relationship with competence, compensation, and workload, as indicated by an R value of 0.921.